Smart Pumping System - A Smart Solution to Automize the Manual Pumping Process - Kurundkar, Sangeeta; Dhandar, Pranav; Boge, Rohan; Doshi, Nisarg; Isapure, Atharv; Mali, Raj (International Journal of Membrane Science and Technology, 2023)
One of the most crucial resources for supporting life on Earth is water. It is necessary for everyday tasks like cooking, cleaning, and taking a shower. Water supply systems in residential areas are often administered by municipal corporations or other governing organizations. This project mainly focuses on the IoT-based solution for the automation of the water tank filling system in our residential area. In this project two Esp8266 MCUs connected to the same cloud channel are used, one will be at the Water Source side and the other will be at the Tank side.If the water level in the tank is low, the Esp8266 will send the Motor ON signal to the ThingSpeak IoT Cloud, and the Esp8266 at the river or dam side, which is also connected to the same cloud channel, will read that signal and turn the ’Motor ON’. The other microcontroller at the river/dam side will turn the motor OFF if the tank is full because the Esp8266 sends the "Motor OFF signal" over the cloud. Additionally, the user is given access to a web interface that shows graphs and indications so they may study and examine the data coming from the system.